EUS-guided intrahepatic biliary drainage: a large retrospective series and subgroup comparison between percutaneous drainage in hilar stenoses or postsurgical anatomy - Giuseppe Vanella; Michiel Bronswijk; Geert Maleux; Hannah van Malenstein; Wim Laleman; Schalk Van der Merwe (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasound-guided intrahepatic biliary drainage (EUS-IBD) struggles to find a place in management algorithms, especially compared to percutaneous drainage (PTBD). In the setting of hilar stenoses or postsurgical anatomy data are even more limited. Patients and methods All consecutive EUS-IBDs performed in our tertiary referral center between 2012 – 2019 were retrospectively evaluated. Rendez-vous (RVs), antegrade stenting (AS) and hepatico-gastrostomies (HGs) were compared. The predefined subgroup of EUS-IBD patients with proximal stenosis/surgically-altered anatomy was matched 1:1 with PTBD performed for the same indications. Efficacy, safety and events during follow-up were compared. Results One hundred four EUS-IBDs were included (malignancies = 87.7 %). These consisted of 16 RVs, 43 ASs and 45 HGs. Technical and clinical success rates were 89.4 % and 96.2 %, respectively. Any-degree, severe and fatal adverse events (AEs) occurred in 23.3 %, 2.9 %, and 0.9 % respectively. Benign indications were more common among RVs while proximal stenoses, surgically-altered anatomy, and disconnected left ductal system among HGs. Procedures were shorter with HGs performed with specifically designed stents (25 vs. 48 minutes, P = 0.004) and there was also a trend toward less dysfunction with those stents (6.7 % vs. 30 %, P = 0.09) compared with previous approaches. Among patients with proximal stenosis/surgically-altered anatomy, EUS-IBD vs. PTBD showed higher rates of clinical success (97.4 % vs. 79.5 %, P = 0.01), reduced post-procedural pain (17.8 % vs. 44.4 %, p = 0.004), shorter median hospital stay (7.5 vs 11.5 days, P = 0.01), lower rates of stent dysfunction (15.8 % vs. 42.9 %, P = 0.01), and the mean number of reinterventions was lower (0.4 vs. 2.8, P < 0.0001). Conclusions EUS-IBD has high technical and clinical success with an acceptable safety profile. HGs show comparable outcomes, which are likely to further improve with dedicated tools. For proximal strictures and surgically-altered anatomy, EUS-IBD seems superior to PTBD.